Emotion regulation and academic performance among IIUM students: a preliminary study - Nur Hafizah Abd Halim Hafiz, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Emotion regulation and academic performance are two important domains in achieving students’ life’s goals and objectives. It is crucial for students to have the right attitude and be fortified with effective emotion regulation strategies to handle the difficulties of daily life. Thus, a study to investigate the relationship between emotion regulations strategies, namely cognitive reappraisal and expressive suppression, and academic performance was carried out. Participants of the study comprised of 127 Psychology students, between the age of 21 to 25 years old, from international Islamic University Malaysia. A survey adapted from Emotion Regulation Questionnaires (ERQ) by Gross (2011) was distributed to the participants.Academic performance measures was derived from demographic background and students’ CGPA. Results revealed that there are different findings between the two emotion regulation strategies. This study found there is a significant relationship between Expressive Suppression and CGPA ; however, no significant relationship existed between Cognitive reappraisal and CGPA. Regression model revealed that both cognitive reappraisal and expressive suppression did not predict students’ academic performance.